Phased Array Technique for Brain Source Localization - Zarghami, Tahereh (2012)
A Master of Science thesis in Electrical Engineering by Tehereh Zarghami entitled, "Phased Array Technique for Brain Source Localization," submitted in January 2012. Available are both soft and hard copies of the thesis.